2018
DOI: 10.1111/all.13456
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular blocking agents induced anaphylaxis: Results and trends of a French pharmacovigilance survey from 2000 to 2012

Abstract: Suxamethonium and rocuronium are markedly more involved in perioperative anaphylaxis than the other available NMBAs. Patients should be more informed about their perioperative anaphylaxis and its consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…A nationwide analysis in France over the period 2000-2012 and published in 2018 that followed the occurrence of post-administration anaphylactic reactions of suxamethonium and rocuronium versus atracurium or cisatracurium found the involvement of suxamethonium in 64% of the adverse reactions (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nationwide analysis in France over the period 2000-2012 and published in 2018 that followed the occurrence of post-administration anaphylactic reactions of suxamethonium and rocuronium versus atracurium or cisatracurium found the involvement of suxamethonium in 64% of the adverse reactions (40).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we wondered if it would justify skin testing of all patients preoperatively. The Petipain study considers that skin tests should be performed more frequently in order to prevent allergic post-muscle relaxant reactions ( 40 ). Sánchez Palacios considered that testing for all patients was not justified due to the small number of patients who had allergic reactions ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects associated with histamine release are flushing and erythema. Less commonly, more severe adverse effects can occur and include tachycardia, bradycardia, hypotension, dyspnea, bronchospasm, urticaria, laryngospasm or wheezing 12 . Studies have previously demonstrated that a MAP fall of 30mmHg can be seen within 2 minutes of administration.…”
Section: S847mentioning
confidence: 99%
“…The results and trends of a French pharmacovigilance survey from 2000 to 2012 on neuromuscular blocking agent (NMBA)‐induced anaphylaxis were recently reported . Among all the available drugs in the French pharmacovigilance database, suxamethonium and rocuronium had a 10‐fold higher risk of perioperative anaphylaxis compared to the other NMBAs.…”
Section: Drug Allergymentioning
confidence: 99%